Analisis Penerimaan Matakuliah Zahir Untuk Mahasiswa Menggunakan Metode Anfis - Minda Septiani (JURNAL TEKNIK KOMPUTER AMIK BSI, 2018)
–  In the world of college education, the course plays an important role in developing the assessment of the student's personality also. Education is a process that accepts input in the form of a student with a low level of understanding, then trained through beberpa stages to produce qualified individuals. Assessment of students to the understanding of the subjects taught is determined by a process of learning and course material provided by the college. Student satisfaction in the process of receiving a course ZAHIR shows the quality of teaching carried out, the satisfaction of student assessment also indicates whether the subjects were given indicates the quality of the learning process and can be accepted by the students themselves. In this study, the research model was built based modeling Adaptive Neuro Fuzzy Inference System (ANFIS) is used to determine student satisfaction based on a syllabus based ZAHIR, which resulted in RMSE of 1.3213e-006 with 300 epoch. Key Word: ZAHIR, Adaptive Neuro Fuzzy  Inference System